Tissue engineering: an Islamic perspective - Sha'ban, Munirah; Mohamad Sukri, Norhamiza (IIUM Press, 2014)
..."Islam encourages seeking remedy and treatment as the Prophet SAW is reported to have said: “There is a cure for every illness, though we may not know it yet?” (Al-Bukhari, al-Sahih, Kitab al-Tib). Therefore, Muslims are encouraged to explore the new treatment methods and the use of such new methods, if proven successful, is strongly recommended. Apart from the evaluation of chances, promises and risks of a new technique, another essential responsibility of ulama’, scientists and ethicist is to check the alternatives. The current trend of using tissue engineering technology seems to be the new alternative for cell and tissue transplantation for treatment of various diseases. Within the past 20 years, the creation of bioartificial tissues via this technology has evolved and achieved a series of successes. Many research findings have indicated that the solutions tissue engineering provides are long-term, much safer than other options and cost-effective as well. Other than that, the transplantation complications are minimized, the donor can be the patient’s own self, the need for donor tissue is minimal, the elimination of immunosuppression problems is a great advantage and the presence of residual foreign material is also eliminated (Atala 2006; Petersen 2008; Shaikh 2010; Ruszymah 2011). Major issues and challenges in tissue engineering are much related to cell isolation and preparation, biomaterial design, the optimization of nutrient transport and transplantation complexity. These include some technical difficulties in active seeding, and to grow cells in sufficient quantities, there may be obstacles to induce cells differentiation into the desired cell type and to ensure the blood and nutrient supply after implantation in the body. Other difficulties scientists may encounter include the unavailability of autologous cells, the time necessary for cells to develop in culture before they can be used, and possible lack of function at the donor site. In addition, the ethical controversies surrounding the harvesting of cells from embryonic sources should not be overlooked. People who believe life starts at conception find it hard to accept that human ova be destroyed for embryonic stem cell production. Next, another ethical dilemma surrounds therapeutic cloning, another technique used to produce stem cells that can also be employed towards the production of clones of beings. Adding to this dilemma, there are ethical concerns about xenotransplantation; a delicate issue of the use of animals for tissue or organ generation. Thus, it is believed that the assessment of tissue engineering from the religious and ethical point of view is complex, depending on the intended goals, the kind of subject, as well as applied techniques. Certainly, there is a lot of issues need to be refined in establishing ethic codes for tissue engineering (Trommelmans 2007)."...